2020
DOI: 10.4103/joacp.joacp_184_17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of postoperative analgesic efficacy and perioperative hemodynamic changes with low dose intravenous dexmedetomidine infusion in patients undergoing laparoscopic cholecystectomy – A randomised, double-blinded, placebo-controlled trial

Abstract: Background and Aims:Recently, low-dose intravenous (IV) dexmedetomidine has been evaluated for obtunding the pneumoperitoneum-induced haemodynamic changes and its analgesic efficacy in laparoscopic cholecystectomy. The aim was to determine the postoperative analgesic efficacy of low-dose bolus of 0.5 μg/kg dexmedetomidine via IV and intraperitoneal (IP) route in laparoscopic cholecystectomy.Methods:Seventy-five patients, aged 18–60 years of ASA physical status I and II, undergoing laparoscopic cholecystectomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 26 publications
0
22
2
Order By: Relevance
“…Continuous infusion of dexmedetomidine during surgery further affected postoperative recovery time and extubation time compared with preoperative bolus infusion. In the previous study, it was found that patients with continuous intravenous infusion of dexmedetomidine 0.5μg/kg/h were still under deep sedation 15 min after entering PACU [ 22 ]. This is also the reason for using slow bolus infusion (10 min) rather than continuous infusion during surgery in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous infusion of dexmedetomidine during surgery further affected postoperative recovery time and extubation time compared with preoperative bolus infusion. In the previous study, it was found that patients with continuous intravenous infusion of dexmedetomidine 0.5μg/kg/h were still under deep sedation 15 min after entering PACU [ 22 ]. This is also the reason for using slow bolus infusion (10 min) rather than continuous infusion during surgery in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, decreases in pain scores over time were also likely to mask differences between groups. Based on the pharmacological profile of agonists of α 2 -adrenergic receptors, it is possible that the BDG could produce better analgesia than BG at later time points (e.g., 16 h) considering the ability of these drugs to produce local vasoconstriction and prolong the anesthetic effect of local anesthetics as demonstrated in humans (1418). Hence, the lack of difference between groups at 24 h should be interpreted with caution because the administration of meloxicam might have confounded these results.…”
Section: Discussionmentioning
confidence: 99%
“…For pain control, topical anaesthetics and opioid analgesics are utilized (Carpenter et al, 2004;Yazbek and Fantoni, 2005;Campagnol et al, 2012;Morgaz et al, 2013). Lambertini et al, 2018;Chilkot et al, 2019). Furthermore, intraperitoneal administration has been employed to control abdominal postoperative pain in human and veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, intraperitoneal administration has been employed to control abdominal postoperative pain in human and veterinary medicine. For intraperitonael administration, a local anaesthetic or analgesic is applied to the surgical site and the viscera before suturing the abdominal wall (Carpenter et al, 2004;Ng et al, 2002;Golubovic et al, 2009;Campagnol et al, 2012;Guerrero et al, 2016;Lambertini et al, 2018;Chilkot et al, 2019). Today, intraperitoneal administration of topical anaesthetics is a valuable and approved method for controlling postoperative pain (Chilkot et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation